THE DEVELOPMENT OF AIR-THEME INTEGRATED SCIENCE TEACHING MATERIAL USING FOUR STEPS TEACHING MATERIAL DEVELOPMENT - Arifin, A.; Sjaeful, A. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
The purposes of this study are to develop, to test the feasibility, to describe the characteristic, and to test the students understanding about integrated science teaching material about air using Four Steps Teaching Material Development (4S TMD). The Research and Development method was use to develop integrated science teaching materials which is involvingÂ all science perspectives that are not presented in junior high school science book. The air theme was chosen in this study since it can be explained using biology, chemistry, physics, and earth and space scienceÂ perspectives. Development the teaching materials was consists of selection, structuring, characterization, and reduction didactic steps. Based on the of feasibility test results, the teaching material is qualified in content, presentation, language, and graphic feasibility aspects. The characteristic of this teaching material expose the closeness theme with student daily lifes and its compatibility with National Books Standard. Based on the understanding test results, the teaching material is qualified in understanding aspect with high category. It can be concluded that the teaching material qualified to be used as supplement teaching material of science learning.Penelitian ini bertujuan untuk mengembangkan, menguji kelayakan, memaparkan karakteristik, dan menguji keterpahaman bahan ajar IPA terpadu pada tema udara untuk siswa SMP kelas VII melalui Four Steps Teaching Material Development (4S TMD). Penelitian dengan metode Research and Development (R&D) ini dilatar belakangi oleh tidak tersedianya bahan ajar IPA SMP yang disajikan secara terpadu melalui tema udara. Pengembangan bahan ajar IPA terpadu tema udara terdiri dari tahap seleksi, strukturisasi, karakterisasi dan reduksi didaktik. Berdasarkan uji kelayakan, bahan ajar telah memenuhi aspek kelayakan isi, kelayakan penyajian, kelayakan bahasa dan kelayakan kegrafikan. Karakteristik bahan ajar meliputi kedekatan tema bahan ajar dengan siswa, dan kesesuaian bahan ajar dengan standar BSNP. Berdasarkan uji keterpahaman, bahan ajar telah memenuhi aspek keterpahaman dengan kategori tinggi. Hasil penelitian ini adalah bahan ajar IPA terpadu berupa buku dengan tema udara yang telah melewati empat tahap pengembangan yang dapat digunakan sebagai bahan ajar pendamping pembelajaran IPA.